Family-level correlates of disruptive behavior challenges among children in Southwestern Uganda. (September 2022) - Byansi, William; Namatovu, Phionah; Sensoy Bahar, Ozge; Kiyingi, Joshua; Nabayinda, Josephine; Mwebembezi, Abel; Kivumbi, Apollo; Damulira, Christopher; Nattabi, Jennifer; Namuwonge, Flavia; McKay, Mary M.; Hoagwood, Kimberly; et al.
Highlights: Examining key influences in sub-Saharan Africa is important to guide investments in child mental health and family support. Parental supervision, widowhood, and family size are significantly associated with child behavioral challenges in Uganda. Study results also suggest that children living in divorced or widowed families may benefit from additional family-level support. Caregivers may also benefit from programs that provide tools for effective parental supervision. Contextually relevant family strengthening interventions may be considered to address child behavioral challenges in Uganda. Abstract: Introduction: This exploratory study sought to examine the extent to which family-level factors are associated with disruptive behavioral disorder (DBD) symptoms, including oppositional defiant disorder (ODD) and conduct disorder (CD) among school children in Uganda, a low-resource country in SSA. The examination of key influences within the SSA context is important to guide needed investments in mental health care and family-level support. Importantly, identifying families at higher risk can inform the development of contextualized family interventions that reinforce positive parenting practices. Method: We analyzed baseline data (N = 2110) from the NIH-funded Strengthening Mental health And Research Training in Africa (SMART Africa) scale-up study in Southwestern Uganda. Children aged 8–13 and their caregivers were recruited from 30 public primary schools. DBDs were examined using the DBD rating scale, Iowa Conners, and Impairment scales. Logistic regression analysis using cluster adjusted robust standard errors to adjust for within-school clustering was conducted to assess the association between DBD symptoms and family-level factors, including parenting practices, marital status, and family size. Results: Results indicate that poor parental supervision (OR = 1.17; CI: 1.13, 1.21; P <.001), divorced families (OR = 1.33; CI: 1.03, 1.72; P <.05), and widowed families (OR = 1.48; CI: 1.10, 2.00; P <.01) were associated with higher DBD symptoms among children. On the other hand, caregiver age (OR = 0.99; CI: 0.98, 0.99; P <.01) was associated with lower DBD symptoms among children. Moreover, caregiver employment and parental education were not statistically significant in the model. Conclusion: Findings from the study reveal an association between family-level factors and behavioral difficulties among children in Uganda suggesting that divorced and widowed families may benefit from additional support in caring for children. Moreover, caregivers may also benefit from programs that provide tools for effective parental supervision.